Harmonizing Existence: A Screenplay on Maintaining Inner Principles Through Habitus in Different Social Circles - Yuehan Imanuel Rumalutur (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
This thesis presents "Harmonizing Existence," a creative drama screenplay exploring socioeconomic inequality, determination, and personal growth through Bourdieu's habitus theory. It follows Joko Damar's journey from poverty to success, highlighting his trials and transformation. Using a slice-of-life approach, the screenplay conveys that success is achievable through adaptation, hard work, and transcending societal limitations. It challenges biases, inspires self-belief, and prompts reflection on individual potential. The narrative examines the interplay between social structures and personal agency, showcasing Joko's navigation of his initial habitus. By depicting his evolving mindset and skills, the story celebrates resilience while critiquing systemic barriers to social mobility, encouraging viewers to consider their growth potential and broader societal implications.